The use of computer aided tools for prototyping in traditional ceramics production in Malaysia. - Olalere, Folasayo Enoch; Ab. Aziz Shuaib (2012)
A prototype is often used as part of product design to allow engineers and designers the ability to explore design alternatives, test theories and confirm performance prior to starting production of new product. The use of computer applications has impacted significantly in the execution of technological innovation in almost all the spheres of industrial design products development. Computer aided design (CAD) in ceramics production has been expressed through conceptualization of ideas to realization of processes in the production of ceramics prototypes that utilize drawing seed, quality production, quick modification, production innovation, cost and time effectiveness. Therefore, this paper attempts to review how computer aided applications have become very relevant in area of ceramic manufacturing such as traditional ceramics. It illuminates on the viability of computer aided tools in enhancing prototyping in traditional ceramic production. This was achieved by first visiting three ceramic factories in Kelantan, Malaysia so as to know the conventional method they used for prototyping. This method was then reviewed by integrating CAD tools into the development cycle. The exploration and development of the vast potentials of computer aided tools for ceramic design and manufacturing will in no doubt fast-track the development of local ceramics production in Malaysia. Besides, the product from well-conceived design ideas and computer aided ceramic manufacturing will contribute significantly to the development of built environment.